INFORMAL VIOLENCE IN SECONDARY SCHOOLS - Mikanović, Brane R; Maran Marijana М (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
Various forms of formal and informal violence can be found in secondary schools. Situations in which only one form of violence is present are rare; informal violence often preceds various forms of formal violence and the other way round. Investigations concerning informal violence in relation to formal violence, at least in terms of pedagogical research, is somewhat lacking. Analysing the sample of 440 secondary school students, the authors identified the presence of: rumours, provocation, segregation, marginalization, media abuse and media insulting. Varying content of manifested violence was identified at the core of these forms of informal violence. The results of empirical investigation can serve future authors and practitioners to create programmes of preventative action to suppres various forms of violence in school and outside it. In addition, the findings can be used for the development of various quantitative and qualitative pedagogic-methodological approaches to the investigation of informal violence in educational institutions.